Strategic planning of business organizations as a tool for forming a stable high-performance production - V. A. Vernikov (Путеводитель предпринимателя, 2020)
The theme of this article is relevant because the development of market relations requires new strategic and conceptual approaches to improving the system of economic relations and creation on this basis of a stable efficient production. The formation of on-farm market economy involves the development of initiative, independence and entrepreneurial spirit, creating a need in the education market psychology workers of the main production.